1995
DOI: 10.1016/s0022-5223(95)70402-7
|View full text |Cite
|
Sign up to set email alerts
|

Innominate artery pseudoaneurysm presenting as a widend mediastinum

Abstract: Hypothermic retrograde cerebral perfusion has been a successful method of cerebral protection during aortic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Studies have shown that IAA is mainly caused by atherosclerosis; however, other causes may include vasculitis, either infectious like syphilis or tuberculosis [4][5]. A study reported that among 120 patients with IAA, the etiology was unknown in 58.3% [6][7]. IAA represents 3% of supra-aortic vessel aneurysms and can lead to devastating complications [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that IAA is mainly caused by atherosclerosis; however, other causes may include vasculitis, either infectious like syphilis or tuberculosis [4][5]. A study reported that among 120 patients with IAA, the etiology was unknown in 58.3% [6][7]. IAA represents 3% of supra-aortic vessel aneurysms and can lead to devastating complications [8].…”
Section: Discussionmentioning
confidence: 99%
“…IAA represents 3% of supra-aortic vessel aneurysms and can lead to devastating complications [8]. The rupture rate is 11% in these patients, especially when the diameter exceeds 3 cm, in which case the risk of rupture will be higher [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic clues of thoracic vascular injury include widening (> 8 centimeters) of the superior mediastinum, apical pleural capping, obscuration of the aortic knob, fractured first rib, depression of the left main bronchus (> 140 degrees from trachea) and deviation of nasogastric tube in the esophagus away from the midline 9 …”
Section: Discussionmentioning
confidence: 99%
“…140 degrees from trachea) and deviation of nasogastric tube in the esophagus away from the midline. 9 In a hemodynamically stable patient, angiography is mandatory. Computerized tomography and magnetic resonance imaging (MRI) are not recommended because they provide only circumstantial evidence of aortic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Em virtude dos fatos relatados, o diagnóstico das lesões supra-aórticas está diretamente ligado a exames subsidiários, em especial radiografia simples de tórax e angiografia 3,13,15,16 , como foi feito no caso relatado. As principais alterações na radiografia são o alargamento em mediastino superior (63%), fraturas de costela, clavícula, pneumotórax, derrame pleural, aumento da inclinação do brônquio fonte esquerdo, hematoma extrapleural, entre outros 10,15,16,18 . A angiografia é o principal método responsável por 77% dos diagnósticos 15 , sendo considerado o exame padrão 3,13,15,16 .…”
Section: Discussionunclassified